A smart healthcare system for measuring and monitoring psychophysiological parameters in humans (Journal of Pharmaceutical Negative Results, 2023)
Evaluation of psychophysiological parameters of human can benefit doctors and physicians to make effective treatment. In this research, a specialized framework for assessing key psychophysiological factors has been delivered. The psychophysiological data was collected from nine persons. In present study, the key psychophysiological parameters such as meditation and attention level of participants have been evaluated using EEG-based brain-sensor.  In addition, a pulse sensor was used for measuring live heartbeats. The results suggest that pulse rate sensor and the EEG sensor can act as efficient interface to assess human’s psychophysiological parameters.